Safety of live attenuated influenza vaccine (LAIV) in children with moderate to severe asthma - Turner, Paul J. (J Allergy Clin Immunol, 2020)
BACKGROUND: Live attenuated influenza vaccine (LAIV) is recommended for annual influenza vaccination in children from age 2 years. However, some guidelines recommend against its use in children with asthma or recurrent wheeze due to concerns over its potential to induce wheezing. OBJECTIVE: We sought to assess the safety of LAIV in children with moderate to severe asthma, and in preschool children with recurrent wheeze. METHODS: Prospective, multicenter, open-label, phase IV intervention study in 14 specialist UK clinics. LAIV was administered under medical supervision, with follow-up of asthma symptoms 72 hours and 4 weeks late, using validated questionnaires. RESULTS: A total of 478 young people (median, 9.3; range, 2-18 years) with physician-diagnosed asthma or recurrent wheeze were recruited, including 208 (44%) prescribed high-dose inhaled corticosteroids and 122 (31%) with severe asthma. There was no significant change in asthma symptoms in the 4 weeks after administration (median change, 0; P = .26, McNemar test), with no impact of level of baseline asthma control/symptoms in predicting either a worsening of asthma or exacerbation after LAIV using a regression model. A total of 47 subjects (14.7%; 95% CI, 11%-19.1%) reported a severe asthma exacerbation in the 4 weeks after immunization, requiring a short course of systemic corticosteroids; in 4 cases, this occurred within 72 hours of vaccination. No association with asthma severity, baseline lung function, or asthma control was identified. CONCLUSIONS: LAIV appears to be well tolerated in the vast majority of children with asthma or recurrent wheeze, including those whose asthma is categorized as severe or poorly controlled.